Assessment of heuristics for self-stabilisation in real-time interactive communication overlays. (2018) - Nuño, Pelayo; Granda, Juan C.; Suárez, Francisco J.
Self-stabilisation is an autonomic behaviour closely related to self-healing. In multimedia communication overlays, self-stabilisation copes with network disruptions by dynamically restoring data links and communication paths. The restoration of links may require reorganisation of the overlay by establishing new connections among members or by modifying existing ones. Selfstabilisation techniques are usually triggered asynchronously, either on use (during reorganisation of the overlay) or on event (as a response to a failure), and several heuristics may be used when selecting link peers. This work assesses several heuristics to perform on event self-stabilisation in multimedia communication overlays. A real-time communication overlay deployed following a fullmesh topology interconnecting a set of multicast islands is used as the assessment framework to evaluate the proposed heuristics. Intensive tests have been carried out to compare and assess heuristics with several overlay configurations and network conditions.